2007
DOI: 10.1002/ijc.22722
|View full text |Cite
|
Sign up to set email alerts
|

SELDI‐TOF MS versus prostate specific antigen analysis of prospective plasma samples in a nested case–control study of prostate cancer

Abstract: There is an urgent need for better biomarkers for detection of clinically significant prostate cancer (PCa). Recent studies suggest that surface enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF MS) analysis of serum may provide diagnostic information. The aim of this study was to investigate if PCa cases could be identified by applying predefined SELDI-TOF analysis conditions on prospectively, uniformly collected plasma samples from PCa cases and matched controls. Prospective sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Biomarkers, especially biomarker patterns, are considered to be reliable and powerful tools for the early diagnosis, differential diagnosis, and therapy of some diseases [18,19] . Analysis of serum proteins by SELDI-TOF-MS provides new information about small proteins with high serum abundances [20,21] .…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers, especially biomarker patterns, are considered to be reliable and powerful tools for the early diagnosis, differential diagnosis, and therapy of some diseases [18,19] . Analysis of serum proteins by SELDI-TOF-MS provides new information about small proteins with high serum abundances [20,21] .…”
Section: Discussionmentioning
confidence: 99%
“…Surface-assisted laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS), which generated the protein fingerprint by MS, has been proved a powerful tool for potential biomarker discovery (Tomosugi 2004;Luo et al 2008). Recently, the SELDI-TOF-MS analysis has been successfully used to identify specific biomarkers for various cancers, such as ovarian cancer (Wang et al 2008), prostate cancer (Skytt et al 2007), pancreatic cancer (Liu et al 2008), colon cancer (Hundt et al 2007), etc. Several studies have reported the potential of SELDI to provide serum biomarkers that differentiate breast cancer from benign disease and healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some abnormal proteins had been discovered in serums of cancer patients [4] , but their practical value had not been fully elucidated [5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…LNCap and DU145 cells (5h10 6 ) were separately incubated in RPMI-1640 medium with or without serum. Forty-eight hours later, the cells were digested and centrifuged.…”
Section: Quantitative Detection For Intracellular Proteinsmentioning
confidence: 99%